Pertanggungjawaban Pidana Pelaku Tindak Pidana Pencabulan Terhadap Anak Di Bawah Umur - Nugroho, Muhammad Arighi; Lewoleba, Kayus K. (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2024)
One type of moral crime is molestation, which is committed against adults and often minors. Children who are victims of crimes, whether directly or indirectly, experience various physical and non-physical disturbances. Sexual crimes also often occur in workplaces, offices, or other places where people of different genders communicate with each other, even within families. The increasing trend of sexual crimes against adult women and minors is quite concerning. The method used is normative juridical. This is used to determine how the principles and standards contained in legislation are applied.